Growing indications for CEUS: The kidney, testis, lymph nodes, thyroid, prostate, and small bowel. Issue 9 (September 2015) - Cantisani, V.; Bertolotto, M.; Weskott, H.P.; Romanini, L.; Grazhdani, H.; Passamonti, M.; Drudi, F.M.; Malpassini, F.; Isidori, A.; Meloni, F.M.; Calliada, F.; D'Ambrosio, F.
Highlights: Contrast enhanced ultrasonography (CEUS) is increasingly used for non-hepatic applications. There is a growing clinical use for a variety of pathologies of the kidney, testis, and small bowel. Updated knowledge for proper use of CEUS in uncommon fields is provided. Abstract: Contrast enhanced ultrasonography (CEUS) is increasingly used for non-hepatic applications as well, so that nearly all organs have been investigated. Among them, there is a growing clinical use for a variety of pathologies of the kidney, testis, and small bowel. The possibility to differentiate benign from malignant nodes in cancer patients has been investigated. A new application is in the detection of sentinel nodes after intradermal microbubble injection. The need to distinguish thyroid nodules eligible for fine needle aspiration cytology has led to the use of CEUS in thyroid examinations as well. The potential of CEUS for prostate cancer detection has been extensively investigated, with encouraging initial results. Early promise, however, has not been fulfilled. New perspective regards evaluation of the extent of prostate tissue devascularization following ablative treatments.